Secure Remote Access in CloudStack: Implementation and Performance Evaluation of an L2TP-over-IPsec VPN - Dileep Domakonda (The Eastasouth Journal of Information System and Computer Science, 2023)
This paper presents the design and deployment of a remote access VPN function in CloudStack, an open-source platform for virtualized cloud management. The Remote Access VPN offers secure connectivity for remote users to communicate with virtual machines (VMs) within guest networks. Users can safely connect to cloud-based systems from external networks by using a VPN that uses L2TP-over-IPsec as the underlying protocol. With certain routing mechanisms that guarantee that only guest network traffic is routed through the VPN, the feature supports both "Road Warrior" (dynamic IP clients) and "Site-to-Site" (pre-configured IP clients) VPN connections. In addition to discussing upcoming scalability and usability improvements, this paper covers the technical design, implementation, and testing strategies for the Remote Access VPN feature.